Adsorption and inhibition properties of mild steel corrosion in ground water medium by 1‐(4‐methoxy benzyl)‐1H‐imidazole: experimental and theoretical investigations. (27th September 2012) - Gopi, D.; Surendiran, M.; Sudha, N.; Saraswathy, R.; Madhammal, R.; Kavitha, L.
<x xml:space="preserve">Abstract</x> Corrosion inhibitive performance of a newly synthesized imidazole derivative 1‐(4‐methoxy benzyl)‐1H‐ imidazole (MBI) on mild steel in ground water medium was investigated. Gravimetric and electrochemical measurements incorporated with quantum chemical calculation were used to study the corrosion inhibition characteristics of MBI in ground water medium. The inhibition efficiency increased with the increase of inhibitor concentration, while the adsorption followed the Langmuir isotherm. To clarify the inhibition efficiency of MBI for the corrosion prevention of mild steel in ground water medium, a density functional theory study was also carried out using 6‐31 G* basis set. Quantum chemical descriptors such as the energy of highest occupied molecular orbital, energy of lowest unoccupied molecular orbital, chemical potential (Pi), electronegativity (χ), global hardness (η), softness (σ), the energy gap (ΔE), and dipole moment (μ) were calculated. The quantum chemical calculations based on density functional theory results show that the new imidazole derivative can adsorb on the mild steel surface, which forms a barrier against corrosion. Thus, MBI acts as a good corrosion inhibitor for mild steel in ground water medium. Copyright © 2012 John Wiley & Sons, Ltd.